PERSPECTIVES TO THE LIBERALIZATION OF THE AGRICULTURAL LAND MARKET IN UKRAINE - ZRYBNIEVA, IRYNA; ZAVOLICHNA, TETYANA (Baltic Journal of Economic Studies, 2017)
The liberalization of Ukrainian agricultural land market does not lose their relevance in the process of the European integration. Ukraine’s transition to the free market of agricultural land requires a theoretical substantiation. The scientific research of modern European approaches to the regulation of the agricultural land market is needed. The purpose of this research is an analysis of the formation and development prospects of the agricultural land market, identifying the possible consequences of the moratorium removal on the purchase and sale of agricultural land, and the search for an acceptable variant of further development land reform policy in Ukraine. The theoretical basis and features of the functioning of the agricultural land market of some European countries that will provide the ability to extrapolate these data into Ukrainian practice are explored in this research. It is expected that many trends are common to the markets of the land of Ukraine and neighbouring countries. Fundamentals of forming effective and transparent agricultural land market require the creation of understandable and clear mechanisms for the regulation of land use systems at various levels. Methodology. In this research are used historical-comparative and logical-dialectical methods for investigating the theoretical foundations and the main determinations of the agricultural land market in Ukraine. Features of circulation of agriculture land plots in Ukraine are submitted. The authors used a system-structural method and a comparative analysis method to justify and compare the indicators of agricultural land use efficiency in Ukraine and some of the European countries. Results. The economic effect of the prospects of liberalization of the agricultural land market in Ukraine is assessed. The determinate hypotheses about perspectives of agricultural land liberalization in Ukraine are argued. Practical implications. The conducted research allows stating that to date, all risks and fears of land market liberalization are insignificant in comparison with the benefits that Ukraine may have in the coming years. An analysis of international experience shows that the reform of the land market was often conducted during the period of economic crises and it was the liberalization of land markets that facilitated the restoration of economies. This should be an incentive for modern Ukraine, to choose finally an approach to market liberalization of agricultural land as a promising way to effectively implement its resource potential.
Keywords: liberalization of agricultural land market; land relations; land circulation; land evaluation; cumulative effect